Compilation and functional classification of telomere length-associated genes in humans and other animal species - E. V. Ignatieva; N. S. Yudin; D. M. Larkin (Вавиловский журнал генетики и селекции)
Telomeres are the terminal regions of chromosomes that ensure their stability while cell division. Telomere shortening initiates cellular senescence, which can lead to degeneration and atrophy of tissues, so the process is associated with a reduction in life expectancy and predisposition to a number of diseases. An accelerated rate of telomere attrition can serve as a predictor of life expectancy and health status of an individual. Telomere length is a complex phenotypic trait that is determined by many factors, including the genetic ones. Numerous studies (including genome-wide association studies, GWAS) indicate the polygenic nature of telomere length control. The objective of the present study was to characterize the genetic basis of the telomere length regulation using the GWAS data obtained during the studies of various human and other animal populations. To do so, a compilation of the genes associated with telomere length in GWAS experiments was collected, which included information on 270 human genes, as well as 23, 22, and 9 genes identified in the cattle, sparrow, and nematode, respectively. Among them were two orthologous genes encoding a shelterin protein (POT1 in humans and pot-2 in C. elegans). Functional analysis has shown that telomere length can be influenced by genetic variants in the genes encoding: (1) structural components of telomerase; (2) the protein components of telomeric regions (shelterin and CST complexes); (3) the proteins involved in telomerase biogenesis and regulating its activity; (4) the proteins that regulate the functional activity of the shelterin components; (5) the proteins involved in telomere replication and/or capping; (6) the proteins involved in the alternative telomere lengthening; (7) the proteins that respond to DNA damage and are responsible for DNA repair; (8) RNA-exosome components. The human genes identified by several research groups in populations of different ethnic origins are the genes encoding telomerase components such as TERC and TERT as well as STN1 encoding the CST complex component. Apparently, the polymorphic loci affecting the functions of these genes may be the most reliable susceptibility markers for telomere-related diseases. The systematized data about the genes and their functions can serve as a basis for the development of prognostic criteria for telomere length-associated diseases in humans. Information about the genes and processes that control telomere length can be used for marker-assisted and genomic selection in the farm animals, aimed at increasing the duration of their productive lifetime.